Probability parameters and estimated firestone abbott plateau honing curves (2018)
This paper developed a methodology for estimating Abbott-Firestone curves from the roughness parameters of the material probability curves. The surface roughness profile obtained in plateau-honing processes is the superposition of the effects of the two processes used to generate it. At first, a honing is performed with which the characteristics of valleys are generated, honing base, and after this honing base, a finishing honing is performed, a plateau operation to reduce the peaks of the base honing profile without modifying the characteristics of the valleys of the base profile. In the functional behaviour of the surface, the valleys will contribute to the retention of oil and the flat areas will contribute to reducing friction with the oil retained in the valleys and to improving watertightness. To characterize this type of roughness obtained by the superposition of the roughness generated by two processes, material probability curves are suitable, in which the roughness of each process is characterized by the slope of a line, and the point of intersection of both lines corresponds to the transition zone between plateaus and valleys. The roughness parameters other than those of the probability curve do not adequately characterize the roughness obtained by processes such as plateauhoning, since they are calculated on the total height of the roughness profile and do not separate the effects of the processes that have been used to obtain it, which means that the contribution of each of the processes to the roughness profile cannot be differentiated.